„W cieniu madame się zrazu chował, a potem ją monsieur zluzował”. Rosyjskie wychowanie szlacheckich dzieci w I połowie XIX wieku - Wilk, Anna Natalia (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
In the first half of 19th century in Russia, being a child of parents from upper class, was not enough to earn the name of true nobleman. It was only a beginning of the arduous process. From the cradle the offspring was taught that the aristocrat should excel in courage, Western manners and languages, general education, artistic talents and athletics. A true Russian nobleman could not differ in any way from his Western European counterpart. In this paper we analyze the childhood reminiscences of Alexander Pushkin as well as his works understood as an example of the influence of the Western model of upbringing on the personality and development of a Russian noble’s child.